2020
DOI: 10.1063/5.0032740
|View full text |Cite
|
Sign up to set email alerts
|

On the unsteady throttling dynamics and scaling analysis in a typical hypersonic inlet–isolator flow

Abstract: The flow field in a two-dimensional three-ramp hypersonic mixed-compression inlet in a freestream Mach number of M∞ = 5 is numerically solved to understand the unsteady throttling dynamics. Throttling conditions are simulated by varying the exit area of the isolator in the form of plug insets. Different throttling ratios between 0 ≤ ζ ≤ 0.7 in steps of 0.1 are considered. No unsteadiness is observed for ζ ≤ 0.2, and severe unsteadiness is found for 0.3 ≤ ζ ≤ 0.7. The frequency of unsteadiness (f) increases rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…The ideal gas model was used for the calculations, and the Shear Stress Transport (SST) k-ω model was used to model the turbulence [22]. In a previous study in the literature, a RANS solver, based on the SST turbulence model in FLUENT, was successfully applied to the flow with SWBLI, and the results of this study are in good agreement with experimental results [23][24][25][26]. The viscosity coefficient follows the Sutherland formula [27].…”
Section: Methodssupporting
confidence: 57%
“…The ideal gas model was used for the calculations, and the Shear Stress Transport (SST) k-ω model was used to model the turbulence [22]. In a previous study in the literature, a RANS solver, based on the SST turbulence model in FLUENT, was successfully applied to the flow with SWBLI, and the results of this study are in good agreement with experimental results [23][24][25][26]. The viscosity coefficient follows the Sutherland formula [27].…”
Section: Methodssupporting
confidence: 57%
“…However, as explained in the previous sections, bluff-body wake flows or separated flows, especially for two-dimensional cases, validations are scarcely available. Recently, in one of the authors' previous works, the capability of this particular solver is demonstrated in both URANS 55 and DES 56 modes at supersonic speed, where separation is encountered a lot. In line with those studies, validation is done for the bluff body flows like the v-gutters in a sub-sonic duct.…”
Section: Solver Validation In Spatial and Spectral Domainmentioning
confidence: 99%
“…32 However, in the case of vehicles traveling at high speeds within the atmosphere, reducing aerodynamic drag is of utmost importance to enhance its range and efficiency. The spiked forebody in any form, either in missiles 33,34 or engine intakes, 35,36 reduces the overall drag as the spike creates a low pressure, recirculating, dead air region in front of the forebody. The pressure forces acting on the forebody are relatively lower than those acting on a forebody with no spike, resulting in drag reduction.…”
Section: Introductionmentioning
confidence: 99%